2020
DOI: 10.1002/cssc.201903288
|View full text |Cite
|
Sign up to set email alerts
|

Grain Enlargement and Defect Passivation with Melamine Additives for High Efficiency and Stable CsPbBr3 Perovskite Solar Cells

Abstract: The preparation of high‐quality perovskite films with low grain boundaries and defect states is a prerequisite for achieving high‐efficiency perovskite solar cells (PSCs) with good environmental stability. An effective additive engineering strategy has been developed for simultaneous defect passivation and crystal growth of CsPbBr3 perovskite films by introducing 1,3,5‐triazine‐2,4,6‐triamine (melamine) into the PbBr2 precursor solution. The resultant melamine–PbBr2 film has a loose, large‐grained structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 50 publications
1
40
0
3
Order By: Relevance
“…J. Zhu et al used 1,3,5-triazine-2,4,6-triamine (melamine) additive into PbBr 2 precusor solution and fabricated high quality CsPbBr 3 perovskite ms with lower grain boundary. 74 It was observed that a combination formed between lead ions and melamine which produces void free perovskite lm with loose grain size and less defect density. In melamine passivated lms, suppressed recombination of charge carriers was observed due to better energy level matching.…”
Section: Effect Of Additives In Perovskite Precursor Solutionsmentioning
confidence: 99%
“…J. Zhu et al used 1,3,5-triazine-2,4,6-triamine (melamine) additive into PbBr 2 precusor solution and fabricated high quality CsPbBr 3 perovskite ms with lower grain boundary. 74 It was observed that a combination formed between lead ions and melamine which produces void free perovskite lm with loose grain size and less defect density. In melamine passivated lms, suppressed recombination of charge carriers was observed due to better energy level matching.…”
Section: Effect Of Additives In Perovskite Precursor Solutionsmentioning
confidence: 99%
“…To enhance the quality of perovskite films, a variety of additives including ammonium salts, [169][170], nanoparticles [171], polymers [167], Lewis acid or base [172] Ionic liquids [173][174] and have been employed to the precursor solution to bond with the and halogen ionic defects and uncoordinated Pb 2+ . Previously, Yang et al [175] Zhu and coworkers [177] introduced a commonly available additive melamine in PbBr 2 precursor solution to passivate the defects and simultaneously develop the crystal growth of CsPbBr 3 perovskite films. They find out that crystallinity of PbBr is affectively reduced with the introduction of melamine, and a high quality, pinhole free, and large grain size CsPbBr 3 film is prepared (Fig.19a).…”
Section: Additive Engineeringmentioning
confidence: 99%
“…175 Therefore, the passivation of these defects is an efficient approach to improve photovoltaic performance and stability. 176 Carbon quantum dots were used as additive in the LHP layer in order to passivate the crystal defects, improve the crystallinity, increase the grain size, reduce the grain boundary, and, in general, prepare high-quality MAPbI 3 films. 177 The unencapsulted devices with carbon quantum dots additive in LHP maintained 85% of their initial PCE after 20 days in air with humidity of 30% (at 20 1C), while the PCE of PSC with pristine LHP decreased by 44%.…”
Section: Reviewmentioning
confidence: 99%